Full Recovery of recurrent extramammary paget’s disease of the vulva (rEMPD-V) after imiquimod treatment - Vespa Jr, Nelson; Aguiar, Andre; Costa, Ronaldo; Funkazawa, Elza; Souza, Gabriel; Coelho, Francisco; Mercado, Soraia; Osório, Cintia Aparecida (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Although rare, extramammary Paget’s disease (EMPD) is a serious condition because underlying internal malignancy may accompany superficial cutaneous lesions.Extramammary Paget disease is characterised by a chronic eczema-like rash of the skin around the anogenital regions of males and females. Under the microscope it looks very similar to the more common type of mammary Paget´s disease that occurs on the breast. Extramammary Paget disease most commonly occurs in women aged between 50-60 years. Although surgical excision is the generally accepted standard of care for EMPD. The EMPD-V recurrence rates are high despite aggressive surgical intervention, treatment with topical imiquimod 5 percent cream has reportedly been efficacious in clearing lesions.We report the case of a 72-year-old woman with biopsy-proven EMPD-V of the thigh treated successfully with imiquimod application thrice weekly for 6 weeks.